Penerapan Media Pembelajaran Geografi Pada Materi Hidrosfer Berbasis Spatial.io untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X-1 di SMAN 1 Lawang - Elfanda, Bagas Putra; Wahyudi, Adip; Fitriana, Evi; Lestari, Shima Tandya (Cetta: Jurnal Ilmu Pendidikan, 2025)
Effective learning depends on innovative and interesting way of presenting the material to increase students' interest in learning. This study aims to apply Spatial.io learning media on hydrosphere material, as well as improve critical thinking skills of students in class X-1 SMAN 1 Lawang. The method used was class action research (PTK), the subject taken was class X-1 with a total of 34 students. Data taken using pre-test post-test and critical thinking skills of students. The results revealed an increase from pre-test to post-test of 26 students, 8 students experienced the same score from both tests, with none experiencing a decrease. Hypothesis testing using the Wilcoxon Test results obtained Asymp.Sig. (2-tailed) 0.000 <0.05, it can be decided that the alternative hypothesis (Ha) is accepted and rejects the null hypothesis (H0). It can be concluded that there is an influence on the application of Spatial.io learning media on students' ability to understand as evidenced by the pre-test and post-test. In critical thinking skills, 34 students were recorded at a percentage of 66 ≤ P ≤ 100 which is categorized as being at a minimum of medium and a maximum of very high scores. This research shows that virtual reality technology not only improves students' critical thinking skills, but also attracts students' understanding of environmental issues.